(untitled) (Research, Society and Development, 2021)
The sustainability of social housing has been widely discussed due to environmental and social impacts, however, this topic has several areas of study. In this sense, knowledge about sustainable development in civil construction can contribute to the best results in the sector. This article aims to highlight the areas of research and relevant work on sustainability in housing with a focus on the low-income population. Thus, a bibliometric analysis was performed with the support of VOSviewer and CiteSpace II tools. Raw data (publications limited to the period 2017-2021) were extracted from the Web of Science database. European countries had the highest number of publications, with emphasis on England being in the first place. Maps were generated with the authors and references that showed the greatest interactions, highlighting the authors Mullins, D., Fitzpatrick, S. and European Commission, and for the works of Vestergaard and Scanlon, (2014), Mulliner and Smallbone, (2013) and Nicol and Humphreys, (2002). Therefore, verifying the agreement with the areas found. Of the 12 research areas, “housing plan”, “energy assessment” and “adaptive comfort” were the most productive areas, that is, with most published works. The most recent areas were “housing plan”, “circularity in social housing” and “predictive models”, presenting themselves as study trends. A panoramic map of the publications on the analyzed topic and how they are was displayed, with interconnections in networks, instructing future in-depth studies in a particular area of ​​interest or how they relate to each other.